Effect of adding letrozole to gonadotropin on in vitro fertilization outcomes: An RCT - Maryam Eftekhar; Lida Saeed (Shahid Sadoughi University of Medical Sciences, 2020)
Background: Aromatase inhibitors prevent the aromatization of androgens into estrogens, which reduces the negative feedback of estrogen on the hypothalamic-pituitary axis. It is clear that increasing the secretion of follicle-stimulating hormones results in an increased follicular growth. Objective: This study aimed to evaluate the effect of adding letrozole to gonadotropin on in vitro fertilization outcomes in normal responders. Materials and Methods: In this randomized clinical trial, 100 normal responder women candidate for controlled ovarian stimulation were randomly enrolled in two groups (n = 50/each). In the case group letrozole was added to gonadotropin in the antagonist protocol. The control group received the conventional antagonist protocol. The main outcome was clinical and chemical pregnancy; and the second outcomes were the number of mature oocytes, the fertilization rate, estradiol level, and the total dose of gonadotropins. Results: Basic clinical and demographic features were comparable between the groups. Estradiol level on the day of human-chorionic-gonadotropin administration and the total gonadotropin consumption were significantly higher in the control group than the case group (p = 0.045). In addition, the number of MII oocytes was higher (but not significantl) in the case group than the control group (p = 0.09). Moreover, the endometrial thickness was significantly lower in the case group. There were no significant differences in fertilization rate and chemical and clinical pregnancy rates between the two groups. Conclusion: Although adding letrozole to gonadotropin in normal responders reduces the total dose of gonadotropin, it does not improve the pregnancy outcomes.